Influência de teleconexão Pacífico-Atlântico e de modos locais na variabilidade da temperatura da superfície do mar do atlântico equatorial ocidental e impactos sobre a precipitação no Estado do Maranhão - SOARES, Laisa Alves Malheiros (2019)
In this work the intensity of the different phases of the oceanic component of the El Niño - Southern Oscillation (ENSO) phenomenon occurred in the four regions of the Niño of the Equatorial Pacific (EP) was evaluated in order to analyze the influence of strong and moderate ENSO events on seasonal and interannual variability of the sea surface temperature (SST) in the Western Equatorial Atlantic Ocean (WEA), as well as its impacts on the precipitation regime in the state of Maranhão. In addition, the spatial - temporal and spectral variability of SST in the Tropical Atlantic (TA) and AEO were analyzed through the methods of empirical orthogonal functions (EOF), Fourier transform (FT) and Wavelet Transform (WT). Data from the monthly average SST from the global ocean reanalysis of the Simple Ocean Data Assimilation (SODA, version 3.3.1) were used. From the SST data of the regions of Niños 4, 3.4, 3 and 1+2, Tropical North Atlantic (TNA), Tropical South Atlantic (TSA) and WEA Ocean were produced SST anomalies (SSTA) and climatic indexes representative of interannual variability. Climatic composites of SSTA were constructed for the WEA Ocean region representative of the different phases (El Niño x La Niña) and intensities (strong x moderate) and referring to the Niño 3.4 and Niño 3 regions. The results show that, based on the Oceanic Niño Index (ONI), predominated more moderate ENSO events than strong, more La Niña events than El Niño, with the Niño 3.4 region presenting the largest number of ENSO events. The Pearson linear correlation (at lag=0) showed that the TNA (TSA) has a statistically significant positive (negative) correlation, although weak, with the different Niño regions, and negative correlations, especially on the TSA sector, between the climatic compounds of SSTA in WEA Ocean and the Pacific Niño regions. The cross-correlation analysis showed a strong time-lagged correlation (lag= ± 5) between the variability in TA and the ENSO, with SST of the same signal in the TNA after 5 months of the occurrence of an ENSO event, and for the TSA the largest correlations were found in lag= -5. The El Niño (La Niña) events, regardless of the Niño region in the EP, were accompanied by cooling (heating) in the WEA Ocean. The regions of Niño 3 and, secondarily, Niño 3.4 and 1 + 2 were the regions that represented the highest SSTA in WEA Ocean. Regarding to the impact of the SSTA in the WEA Ocean on the precipitation in the state of Maranhão, during El Niño (La Niña) events in the Niño 3.4 and 3 regions, there was a decrease (increase) of precipitation in the state. The Atlantic dipole (AD) signal was evaluated and its positive and negative phases were compared with the ION, in addition, its influence on precipitation in the state of Maranhão was analyzed. This relationship showed a predominance of the positive phase of AD during the El Niño events and the negative phase during La Niña years. The AD configuration occurred from February to May, influencing rainfall in the state of Maranhão during the rainy season (MAM). The pattern observed in the EOF of the filtered and unfiltered SST is consistent with the Equatorial Zonal Mode and the AD pattern. In the spectral analysis of the SST in the TA Ocean, an intense annual cycle was found in the global energy spectrum of the wavelet for the TNA and TSA region and was observed a greater climatic variability in the TNA compared to the TSA.